MENAKAR POTENSI NILAI KEARIFAN LOKAL DALAM SASTRA DAERAH - Achmad Naufal Irsyadi; Nala Maziya Fitriyah; Fachriana Hanifiyah; Muta’allim Muta’allim (Universitas Sebelas Maret, 2023)
Local literature has an important role in globalizing the value and local wisdom of a community. The goal is to preserve and spread benefits for human life. Madurese literature is one of the types of local literature that has developed. The development of Madurese literature that combines religious and social-social elements cannot be separated from the existence of Pesantren. This study aimed to examine the meaning, values, and local wisdom in Madurese literature based on the philosophy of objectivism. Hermeneutics was used to analyze fragments of M. Faizi's poems to find their meaning and value. This study showed that the human value that described the local wisdom of the Madurese in M. Faizi’s poem was a reality. This finding was also supported by a number of studies on Madurese indigenous people. Thus, in addition to having a figurative language, M. Faizi's poems also contained contextual meanings, and this characterized an element of objectivism in his poems.